Nursing staff's instrument for change-of-shift reporting - SBAR (Situation-Background-Assessment-Recommendation): validation and application - Felipe, Tânia Roberta Limeira [UNESP]; Spiri, Wilza Carla [UNESP]; Juliani, Carmen Maria Casquel Monti [UNESP]; Mutro, Maria Eugênia Guerra (FapUNIFESP (SciELO), 2022)
OBJECTIVES: to validate and apply a change-of-shift instrument using the SBAR (Situation-Background-Assessment-Recommendation) tool. METHODS: methodological study for the validation of an instrument. It was validated by ten judges from the area of nursing teaching and care and applied in a surgical gastroenterology ward by 11 nursing technicians in February 2019. The analyses considered descriptive statistics. RESULTS: the judges analyzed the instrument with a content validity index of 91.7% and made suggestions, which led to the second version of the instrument. The participants reported that the predominant modality of shift handover is oral, in the nursing room, lasting six to ten minutes. Most pay attention during shift change, mention that delays and early departures interfere in the activity and believe that the instrument provides the necessary information and is viable. CONCLUSIONS: the instrument built was validated, and its application proved relevant, as it was considered necessary and feasible.